2007
DOI: 10.1002/sat.878
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive power control for satellite to ground laser communication

Abstract: SUMMARYWe develop an adaptive power control algorithm to facilitate satellite to ground laser communication through turbulence fading channels. Adaptive control is a powerful tool that improves energetic gain of the satellite laser. We use discrete laser transmitter intensity levels in our control algorithm. A novel recursive technique defines optimal laser transmitting intensity levels so that the laser-transmitted power is adapted according to instant changes of the signal-to-noise ratio caused by channel fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…4-6 illustrate the average BER performance of the adaptive transmission technique for the same target BER requirements and turbulence conditions. It is clearly depicted that the average BER of the adaptive system is lower than the target P o in all cases examined, satisfying the basic design requirement of (16). Moreover, it can be easily observed that the performance of the adaptive system approaches the performance of the non-adaptive system with the largest modulation order, at high values of average SNR; this was expected, since in this SNR regime the adaptive scheme chooses to transmit with the largest available modulation order.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…4-6 illustrate the average BER performance of the adaptive transmission technique for the same target BER requirements and turbulence conditions. It is clearly depicted that the average BER of the adaptive system is lower than the target P o in all cases examined, satisfying the basic design requirement of (16). Moreover, it can be easily observed that the performance of the adaptive system approaches the performance of the non-adaptive system with the largest modulation order, at high values of average SNR; this was expected, since in this SNR regime the adaptive scheme chooses to transmit with the largest available modulation order.…”
Section: Resultssupporting
confidence: 55%
“…Since then, various adaptive FSO systems have been proposed. In [15], a variable rate FSO system employing adaptive Turbo-based coding schemes in conjunction with On-Off keying modulation was investigated, while in [16] an adaptive power scheme was suggested for reducing the average power consumption in constant rate optical satellite-to-earth links. Recently, in [17], an adaptive transmission scheme that varied both the power and the modulation order of a FSO system with pulse amplitude modulation (PAM), has been studied.…”
Section: Introductionmentioning
confidence: 99%
“…A comparison of bandwidth requirement, PAPR and capacity for variants of PPM modulation schemes is shown in Table VII. Adaptive modulation has also been used in order to improve the spectral efficiency and robustness of the channel in space optical links [279], [294], [295]. The efficiency of the adaptive modulation depends upon the accuracy of channel estimates derived from the received signal strength through a low rate feedback path.…”
Section: From Distant Transmittermentioning
confidence: 99%
“…Apì tìte, difora prosarmosmèna OW sust mata protjhkan. Sthn [64], èna metablhtoÔ rujmoÔ prosarmosmèno OW sÔsthma pou basÐzetai sthn epilog tou katllhlou Turbo k¸dika melet jhke, en¸sthn [65] èna metablht c isqÔoc prosarmosmèno OW sÔsthma protjhke to opoÐo mei¸nei thn katanlwsh thc mèshc isqÔoc stic stajeroÔ rujmoÔ dorufìrou proc epÐgeio stajmì OW zeÔxeic. Tèloc, sthn [66] èna prosarmosmèno sq ma metdoshc exetsjhke, to opoÐo metabllei kai thn mèsh isqÔ kai ton rujmì metdoshc OW susthmtwn pou qrhsimopoioÔn diamìrfwsh pltouc pulse amplitude modulation (PAM).…”
Section: Bibliografik Anaskìphshmentioning
confidence: 99%